Pelaksanaan Senam Lansia dalam Upaya Peningkatan Kesehatan - Isni Hijriana; Yusnita Yusnita (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The aging process (aging process) is a process characterized by a decrease in physical and cognitive function, or also called a degenerative process that involves all organs of the body. Progressive physical decline, decreased functional capacity, and the emergence of many diseases are the physiology of the aging process, the effects of aging on the neuromuscular system are related to degeneration of motor neurons and decreased muscle fibers, the number and size of which will have an impact on loss of muscle performance and will affect the independence of the elderly. Physical activity/exercise is considered as one of the main strategies to ward off physical disorders. The purpose of this service is to conduct counseling and apply elderly gymnastics, so that the elderly understand the importance of physical activity, one of which is elderly exercise which is useful for improving health and preventing the onset of ongoing diseases. The first stage of this activity is providing counseling, then measuring blood pressure before doing gymnastics, then lecturers and students together with the elderly do gymnastics, and after that blood pressure is measured again. The results of this dedication are expected to increase motivation for the elderly to do elderly exercise at least three times a week so as to improve the status of independence of the elderly and the quality of life of the elderly.